Macroeconomic Policy, Product Market Competition, and Growth : The Intangible Investment Channel - Ahn, JaeBin (IMF Working Papers; Working Paper, 2020)
While there is growing evidence of persistent or even permanent output losses from financial crises, the causes remain unclear. One candidate is intangible capital - a rising driver of economic growth that, being non-pledgeable as collateral, is vulnerable to financial frictions. By sheltering intangible investment from financial shocks, counter-cyclical macroeconomic policy could strengthen longer-term growth, particularly so where strong product market competition prevents firms from self-financing their investments through rents. Using a rich cross-country firm-level dataset and exploiting heterogeneity in firm-level exposure to the sharp and unforeseen tightening of credit conditions around September 2008, we find strong support for these theoretical predictions. The quantitative implications are large, highlighting a powerful stabilizing role for macroeconomic policy through the intangible investment channel, and its complementarity with pro-competition product market deregulation.